2017
DOI: 10.5792/ksrr.16.047
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Outcomes of a New Posteriorly Stabilized Total Knee Arthroplasty Prosthesis: Comparisons with Two Established Prostheses

Abstract: PurposeWe sought to determine whether early clinical performance of new posterior stabilized (PS) knee system, the Vega-PS (Aesculap), is better than that of two established total knee arthroplasty (TKA) prostheses, the E.motion-PS (Aesculap) and the Genesis II (Smith & Nephew) in terms of functional outcomes, patient satisfaction, and incidence of adverse events.Materials and MethodsWe compared the clinical outcomes of 206 consecutive TKAs using Vega-PS with those of 205 TKAs using E.motion-PS and 216 TKAs us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…These findings are in contrast to the promising short-term clinical behavior of the Vega PS knee system reported by Jain et al [44]. In 3 cohorts they compared the clinical outcomes of 206 consecutive TKAs using Vega PS with those of 2 clinically long-term established posterior-stabilized designs (e.motion PS n ¼ 205; Genesis II n ¼ 216) in a 2-year follow-up study and found comparable or superior functional clinical performance of Vega PS without incidence of implant-related adverse events [44]. Lionberger et al [48] further hypothesized that the ceramic hardened implant surface may be a potential factor for limited cement adhesion and early debonding in the later loosenings and proposed further testing to ascertain the root cause for these failures, but his cementation technique lists that he was using Palacos R and cementing in the late window we investigated in this study and he also lists 2 other cementation techniques that are specifically contrary to manufacturer recommendations.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These findings are in contrast to the promising short-term clinical behavior of the Vega PS knee system reported by Jain et al [44]. In 3 cohorts they compared the clinical outcomes of 206 consecutive TKAs using Vega PS with those of 2 clinically long-term established posterior-stabilized designs (e.motion PS n ¼ 205; Genesis II n ¼ 216) in a 2-year follow-up study and found comparable or superior functional clinical performance of Vega PS without incidence of implant-related adverse events [44]. Lionberger et al [48] further hypothesized that the ceramic hardened implant surface may be a potential factor for limited cement adhesion and early debonding in the later loosenings and proposed further testing to ascertain the root cause for these failures, but his cementation technique lists that he was using Palacos R and cementing in the late window we investigated in this study and he also lists 2 other cementation techniques that are specifically contrary to manufacturer recommendations.…”
Section: Discussioncontrasting
confidence: 99%
“…They hypothesized that the new design of the Vega PS tibial tray may be a factor to be considered for their unfavorable clinical outcomes [48]. These findings are in contrast to the promising short-term clinical behavior of the Vega PS knee system reported by Jain et al [44]. In 3 cohorts they compared the clinical outcomes of 206 consecutive TKAs using Vega PS with those of 2 clinically long-term established posterior-stabilized designs (e.motion PS n ¼ 205; Genesis II n ¼ 216) in a 2-year follow-up study and found comparable or superior functional clinical performance of Vega PS without incidence of implant-related adverse events [44].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…PS inserts, which have a central polyethylene tibial post articulating with a transverse metal femoral cam, aim to decrease shear forces and wear via the physiologic rollback of the femur on the tibia and by improving anterior–posterior stability [14]. PS inserts provide reliable long‐term fixation and functional improvements [13, 19]. However, PS inserts can lead to unfavourable results, including intercondylar fracture of the distal femur, post‐breakage, post‐dislocation, and patellar clunk syndrome [9, 25].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, enhancements in the range of motion (ROM) and deep knee flexion were expected from MB prostheses due to their more physiological kinematics [13]. However, previous randomized controlled trials [19, 22] and meta‐analyses [13, 17] comparing fixed‐bearing (FB) and MB TKA revealed no significant differences in the clinical or radiographic results, or survival rates, between these prostheses.…”
Section: Introductionmentioning
confidence: 99%